Navicula congqiancuoensis sp. nov. — a new diatom species (Bacillariophyceae) from Sichuan Province, China - Yu-Fei Jiang; Saúl Blanco; Wei Zhang (PhytoKeys)
In this study, we describe a new diatom, Navicula congqiancuoensis sp. nov., which was found in epilithon samples collected from a small mountain lake, at Lake Congqiancuo, Sichuan Province, China. A detailed morphological description of the new species is provided based on light and scanning electron micrographs. Navicula congqiancuoensis sp. nov. valve is linear to linear-lanceolate, with a slight elevation in the center and broadly rounded at both apices. The striae are radiate and convergent at the apices. The axial area is narrow and linear, and the central area is small and elliptical in the middle. This new species is compared with similar species, such as Navicula angusta, N. leptostriata, N. piercei, N. heimansioides which differ in size, valve shape, striae density and ultrastructure.